(untitled) (Eurasian Journal of Ecology, 2016)
The article is devoted to the problem of increase of resistency of cells of an organism at experimental diabetes. It is shown, that at development of a diabetes there is a decrease osmotic and hydroperoxide resistence of erythrocyte membranes, permeability raises, that as a result leads to the injuring of cell integrity. Application of a preparation on the basis of plants on a background of an experimental diabetes allows to lower a level hemolysis.